Sir George R. Parkin & Herbert Marshall McLuhan Making Sense of a ShrinkingWorld - Ralon Facchina, Laureano (International Journal of Canadian Studies / Revue internationale d’études canadiennes, 2009)
AbstractMcLuhan was by no means the first to perceive the shrinking effects ofelectronic technology. Sir George R. Parkin—writing several decades beforeMcLuhan and just eight years after the invention of the telegraph—was wellaware of such effects; however, for various reasons, he failed to comprehend thesignificance of such effects. This paper argues that, unlike Parkin, McLuhan notonly understood the phenomenon of a shrinking world, but he effectively contributedto its realization. It discusses McLuhan's use of clichés in effecting suchphenomenon, as well as his role as a "dative of manifestation", i.e., his being atthe right place at the right time to support the "revealing" of an electronicenvironment that gained momentum in the 1960s and became fully accepted in the1990s, but technically had been in the making since 1880 with the invention of thetelegraph.